Biosynthesis of Iron Nanoparticles Using Tie Guanyin Tea Extract for Degradation of Bromothymol Blue - Haiyan Xin; Xin Yang; Xiaoli Liu; Xueping Tang; Lianjin Weng; Yuanyuan Han (Journal of Nanotechnology)
Facile synthesis of zero-valent iron nanoparticles has been developed using Tie Guanyin tea extract as reducing and stabilizing agent. The characterization carried out by UV-Vis, SEM, TEM, XRD, and FTIR techniques has identified the successful synthesis of the zero-valent iron nanoparticles. It is evident from the TEM result that spherical zero-valent iron nanoparticles with average size of 6.58±0.76 nm have been obtained through biological method in this study. FTIR spectrum demonstrates that the polyphenols play an important role in the synthetic process. Diffraction peak at 2θ of 44.9° and 49.1° in XRD spectrum explains the existence of the iron nanoparticles. Additionally, effect of concentration of iron nanoparticles and concentration of bromothymol blue on the kinetic rate constants during the degradation process was studied.